Spectroscopic evidence for ?-NAT, STS, and ice in MIPAS infrared limb emission measurements of polar stratospheric clouds - Höpfner, M.; Luo, B. P.; Massoli, P.; Cairo, F.; Spang, R.; Snels, M.; Di Donfrancesco, G.; Stiller, G.; von Clarmann, T.; Fischer, H.; Biermann, U. (CCSD, 2005)
International audience We have analyzed mid-infrared limb-emission measurements of polar stratospheric clouds (PSCs) by the Michelson Interferometer for Passive Atmospheric Sounding (MIPAS) during the Antarctic winter 2003 with respect to PSC composition. Coincident lidar observations from McMurdo were used for comparison with PSC types 1a, 1b and 2. By application of new refractive index data we could prove that a spectral signature at 820 cm ?1 as observed by MIPAS near to the observation of a type 1a PSC is due to a composition of ?-NAT. MIPAS infrared spectra collocated with Lidar observations of Type 1b and Type 2 PSCs could only be reproduced by assuming a composition of supercooled ternary H 2 SO 4 /HNO 3 /H 2 O solution (STS) and of ice, respectively. Particle radius and number density profiles derived from MIPAS were generally consistent with the lidar observations. Only in the case of ice clouds, PSC volumes are underestimated due to large cloud optical thickness in the limb-direction. A comparison of MIPAS cloud composition and lidar PSC-type determination based on all available MIPAS-lidar coincident measurements revealed good agreement between PSC-types 1a, 1b and 2, and NAT, STS and ice, respectively. We could not find any spectroscopic evidence for the presence of nitric acid dihydrate (NAD) from any MIPAS observation of PSCs over Antarctica in 2003.